PENGGUNAAN MODEL ARIMAX UNTUK MERAMALKAN DATA CURAH HUJAN BULANAN DI BALI - NISA, CHAIRUN; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 10 No 4 (2021)DO - 10.24843/MTK.2021.v10.i04.p341, 2021)
Erratic raifall in the future has a major effect on life. Extreme rainfall can result in vaarious natural phenomena that have a negative impact in various fields work. The aim of this research is to find the best rainfall forecastng model in Bali using ARIMAX modeling, namely the transfer function model with an indeks Nino 3.4 as the input series. The transfer function model is a time series model that combines the regression approach and the ARIMA model for its error. Forecasting results suggest that the rainfall is linearly related to the Nino 3.4 indeks in the previous month. The best rainfall forecasting model has a value Akaike information criterion (AIC) is equal to .